Synthesis of 4, 4′-bipentacyclo[5.4.0.02, 6.03, 10.05, 9]undecane. Issue 14 (5th April 2017) - Shi, Yijun; Jiang, Jingyang; Ma, Li; Wang, Jianzhi; Li, Wei
Graphical abstract: Highlights: A new synthetic strategy to construct two cages simultaneously was designed. A new bi-cage hydrocarbon was synthesized through a three steps synthetic route. The bi-cage hydrocarbon has high density and high volumetric heat of combustion. The intramolecular [2+2] photocyclization can be carried out in sunlight. Abstract: A new bi-cage hydrocarbon, 4, 4′-bipentacyclo[5.4.0.0 2, 6 .0 3, 10 .0 5, 9 ]undecane (12 ) was designed based on a strategy to construct two cages simultaneously from one key molecule scaffold. Thus12 was conveniently synthesized from 5, 5′-bi(cyclopentadiene) (9 ) through a three steps synthetic route in 23% overall yield. The new bi-cage hydrocarbon has high density (1.2322 g/cm 3 ) and high volumetric heat of combustion (51.670 MJ/L).